High-end physician migration from India - Manas Kaushik; Abhishek Jaiswal; Naseem Shah; Ajay Mahal (The World Health Organization, 2008)
OBJECTIVE: To examine the relation between the quality of physicians and migration among alumni of All India Institute of Medical Sciences (AIIMS), New Delhi, India over the period 1989-2000. METHODS: In a retrospective cohort study, data on graduates of AIIMS were collected from entrance exam qualifier lists, the AIIMS alumni directory, convocation records, the American Medical Association and informal alumni networks. The data were analysed by use of 2x2 contingency tables and logistic regression models. FINDINGS: Nearly 54% of AIIMS graduates during 1989-2000 now reside outside India. Students admitted under the general category are twice as likely to reside abroad (95% confidence interval: 1.53-2.99) as students admitted under the affirmative-action category. Recipients of multiple academic awards were 35% more likely to emigrate than non-recipients of awards (95% confidence interval: 1.04-1.76). Multivariate analyses do not change these basic conclusions. CONCLUSION: Graduates from higher quality institutions account for a disproportionately large share of emigrating physicians. Even within high-end institutions, such as AIIMS, better physicians are more likely to emigrate. Interventions should focus on the highly trained individuals in the top institutions that contribute disproportionately to the loss of human resources for health. Our findings suggest that affirmative-action programmes may have an unintended benefit in that they may help retain a subset of such personnel.